Bottom‐up effects of female strategic leadership: Firm performance effects through employees - Jeong, Seung‐Hwan; Kang, Saehee; Byron, Kris (Strategic Management Journal, 2026)
Abstract Research Summary Scholars have found that female representation in strategic leadership is often positively associated with firm performance, though the underlying mechanisms remain unclear. Prior explanations emphasize top‐down effects, considering how female leaders shape strategic decision‐making or influence legitimacy. We propose a complementary, bottom‐up view: female top managers foster employee participation, which is positively associated with firm performance. Using a unique panel dataset from South Korea, we find that female representation in top management is linked to higher employee participation, which mediates its relationship with firm performance. The benefits of employee participation are especially pronounced in firms with innovation‐oriented or labor‐intensive strategies. By integrating micro‐level employee behaviors with macro‐level firm outcomes, our study shows how female strategic leaders contribute to firm performance through a top‐enabled, bottom‐up process. Managerial Summary Why do firms with more women in top management perform better? Our study suggests that one important pathway lies in how female executives may foster employee participation. Drawing on a unique panel dataset from South Korea, we find that organizations with more women in top management tend to have higher levels of employee participation in decision‐making, and that such participation is associated with stronger performance outcomes. This effect is especially evident in firms that depend on innovation or human capital, where employee input and commitment are particularly valuable. By highlighting how female strategic leaders help create conditions that elevate employee voice, our findings reveal a bottom‐up process through which strategic leadership diversity may support improved organizational performance.